Clinicopathological Correlation of Endometrial Thickness and Ovulatory Patterns in PCOS Women: A Systematic Review and Meta-analysis - Fakhria Ijaz; Roomi Memon; Seema Ashfaque Abro; Tanzeel Shafique Ul Rehman (Pakistan Journal of Medicine and Dentistry)
Background: Polycystic Ovary Syndrome (PCOS) is an endocrine condition that causes trouble with ovulation, increased male hormone levels, and ovaries filled with cysts. The aim of the systematic review and meta-analysis was to provide an evaluation of the effect of polycystic ovary syndrome (PCOS) on the endometrial thickness and histopathological abnormalities in women.